Revision of the Merodon bombiformis group (Diptera: Syrphidae) – rare and endemic African hoverflies - Vujić, Ante; Radenković, Snežana; Šašić Zorić, Ljiljana; Likov, Laura; Tot, Tamara; Veselić, Sanja; Djan, Mihajla (European Journal of Taxonomy, 2021)
In the present work, the Afrotropical species of the bombiformis species group, part of the aureus lineage, are revised. Six species are recognized, based on a combination of morphological and genetic features. Three of these species are new to science: Merodon lotus Vujić & Radenković sp. nov., M. vittatus Vujić & Likov sp. nov., and M. zebra Vujić & Radenković sp. nov. Redescriptions are provided for the other three species: M. bombiformis Hull, 1944, M. multifasciatus Curran, 1939, and M. nasicus Bezzi, 1915. The female of M. bombiformis is described. The name Merodon edentulus Macquart, 1855 is considered here as a nomen dubium. One new synonymy is proposed: M. apimima Hull, 1944 syn. nov. (junior synonym of M. multifasciatus). The distribution of the bombiformis species group is discussed. The larval host plant of M. multifasciatus is identified as Gladiolus. A key to the identification of both males and females of the bombiformis group is provided.